2007
DOI: 10.1029/2006jd008002
|View full text |Cite
|
Sign up to set email alerts
|

Processing of atmospheric nitrogen by clouds above a forest environment

Abstract: ) and organic nitrogen (DON) were measured in cloud water samples collected over the northern lower peninsula of Michigan. Within a given cloud field, several altitudes were sampled to examine changes in concentration and speciation with altitude. Several samples were analyzed for bacterial content and activity. Convective cumulus (cumulus congestus) were more concentrated than fair weather cumulus (cumulus humilis) for all major ions and DON, with the cloudy air DON concentrations in convective cumulus being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 83 publications
(115 reference statements)
2
72
2
Order By: Relevance
“…The same pattern of higher final concentrations can also be seen for NO 3 -. It is known that atmospheric NO 3 -within the Arctic can occur in association with aerosols (Hara et al, 1999;Teinilä et al, 2003) and with bacteria (Hill et al, 2007). If particles and bacteria remain in the snowpack rather than following the meltwater, as our results suggest, an elevated concentration of associated chemicals (such as NO 3 -) might be expected in the remaining snow.…”
Section: Ion Elutionmentioning
confidence: 63%
“…The same pattern of higher final concentrations can also be seen for NO 3 -. It is known that atmospheric NO 3 -within the Arctic can occur in association with aerosols (Hara et al, 1999;Teinilä et al, 2003) and with bacteria (Hill et al, 2007). If particles and bacteria remain in the snowpack rather than following the meltwater, as our results suggest, an elevated concentration of associated chemicals (such as NO 3 -) might be expected in the remaining snow.…”
Section: Ion Elutionmentioning
confidence: 63%
“…A few decades ago, living microorganisms were observed in cloud water (Sattler et al, 2001;Amato et al, 2005Amato et al, , 2007aWei et al, 2017). Particularly through measurements of adenosine triphosphate (ATP) and anabolic precursors or nutrient incorporation rates, it has been shown that cloud microorganisms are metabolically active and play an important role in cloud chemical reactivity (Sattler et al, 2001;Amato et al, 2007a;Hill et al, 2007;Vaïtilingom et al, 2012Vaïtilingom et al, , 2013. Several studies performed on simplified or real microcosms have demonstrated that cloud microorganisms are able to degrade carbon compounds (Ariya et al, 2002;Amato et al, 2005Amato et al, , 2007cHusarova et al, 2011;Vaïtilingom et al, 2010Vaïtilingom et al, , 2011Vaïtilingom et al, , 2013Matulovà et al, 2014); recent studies have also shown that this could be the case in the air (Krumins et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This activity toward organic compounds likely participates in carbon chemistry in clouds. In addition, nitrifying bacteria have been detected in clouds and they could be involved in the transformation of atmospheric nitrogenous species (25). One key objective now is to quantify the importance of the biological oxidation pathways compared to that of chemical and photochemical processes.…”
mentioning
confidence: 99%